A Research on the Visiting Phenomenon of Varto Alevis - Yalçınkaya, Fatoş (Journal of Alevism-Bektashism Studies, 2019)
The pilgrimage phenomenon is an important aspect of folk belief within religious-social life. These pilgrimages are usually called “pir”/“dede”/“baba” tombs or “ziyaret” (sacred places where mountain, tree, stone, and water occur). The aim of the pilgrimage to these sacred places is to ask God for help with the help of some sacred sprits and ensure the help of these sacred spirits in making pilgrims’ wishes come true.After discussing and analysing pilgrimages in Varto and rituals formed around them in the context of relation between sacred places and human, it is ascertained that there is, in general terms, a psychosocial relation between these places and humans.Beliefs belonging to the cultural memory of societies in which rituals practiced around pilgrimage phenomenon are created, figure in the basis of these rituals. The pilgrimages of Varto Alevis are full of elements belonging to mountain, tree, stone and water cults rather than tomb cult. Today, this belief, whose origins lay before monotheistic religions, preserves its liveliness.A person who wishes to relax psychologically and overcome problems, needs sacred places where he will make contact with the divine. These sacred places are, at the same time, places where the divine appears. Pilgrimages, accepted as sacred by society, are made for this purpose. These pilgrimages are also a tool between God and human. The main purpose is to reach Him, to beg and pray Him.This paper discusses and analyses the pilgrimage phenomenon that figures in Varto Alevis’ belief system and largely forms their way of life. It is determined that these pilgrimages/sacred places are an important religious phenomenon in the cultural forming of society. In the paper, the bases of the pilgrimage phenomenon and rituals formed around this belief are discussed by using the phenomenological method.There are 96 villages in Varto. 3 of them, being close to centre of Varto, have become quarters. Therefore, according to official records, there are 93 villages. Alevis live in 44, and in 5 villages live both Alevis and Sunni Muslims. These 49 villages are frame of the study. After presenting the theoretical framework of the study, sacred places in Varto are determined. The author of the paper has participated in pilgrimages as an observer and has personally observed rituals.
Keywords: Varto; Alevi; pilgrimage; phenomenon; sacred place